Análise fitoquímica das espécies Discaria americana e Scutia buxifolia - Dahmer, Janice (2018)
This work had as a proposal to carry out a phytochemical study of the crude extract of the bark of the roots of the species American Discaria Gilles and Hooker and of the bark of the stem of the species Scutia buxifolia. Through this study it was possible to isolate seven compounds of the American Discaria, with known structures, from the Total Alkaloid Ethereal Fractions (FBEAT). The cyclopeptide alkaloids are Discarina-B (42), -C (41) and -D (43), Franfrepholine (46) and Frangulanine (45), Adouetine Y '(47) and also the neutral cycloheptídeo Discareno C ). From the Scutia buxifolia species, the cyclopeptural alkaloids with structures known as Scutianina-P (48) and -N (49), Aralionin B (50), and Scutianenos neutral cyclopeptides were isolated from the Total Alkaloid Ethereal Fractions (FBEAT) -X (13) and -Z (15), two novel substances, the Scutianinas-Q (51) and -R (52) peptides in addition to an amide, (R) - Tamamide (38) which is usually found in plants of the family Rutaceae. Also in the phytochemical analysis was carried out a preliminary quantitative study to verify the seasonality of the production of these compounds in these species. In this study, it was observed that the highest production of cyclopeptide alkaloids are in the winter and summer months for both species. This may indicate that these compounds are produced when the environment offers extreme temperature conditions. In addition, the antimicrobial potential of the cyclopeptide alkaloids and the isolated neutral cyclopeptides in addition to the ethereal basic fractions obtained from the American Discaria and Scutia buxifolia against the five gram-positive bacteria: Bacillus subtilis, Enterococcus spp., Enterococcus fecalis, Staphylococcus aureus, Bacillus cereus and nine gram-negative bacteria: Salmonella typhimurium, Proteus mirabilis, Escherichia coli, Pseudomonas aeroginos, Shigella flexneri, Salmonella enteritidis, Enterobacter aerogenes, Morganella morganii and Shigella sonnei. The results obtained from this evaluation were very satisfactory, since both the FBEAT fractions had an inhibitory potential, ranging from 31,2 μg/ml to 250 μg/ml, in the case of isolates with a Minimum Inhibitory Concentration between 1,56 μg/ml and 100 μg/ml. From the results of the antimicrobial activity, what was most striking was that all samples tested here had both inhibitory and bactericidal potential against Enterococcus spp. Minimum Inhibitory Concentration ranged from 25 μg/ml to 50 μg/ml and Minimum Lethal Concentration between 50 μg/ml and 200 μg/ml for the isolates. For FBEAT, the Minimum Inhibitory Concentration ranged from 62,5 μg/ml to 125 μg/ml and Minimum Lethal Concentration between 125 μg/ml and 250 μg/ml.